Palliative care in locally advanced breast cancer. Clinical case - Marina V. Kiseleva; Maksim S. Denisov; Elena V. Litvyakova; S.A. Ivanov; A.D. Kaprin; Mariya N. Lun'kova (LLC "MEDIAFORMAT", 2023)
Despite introduction of new screening programs and emergence of novel anticancer drugs, the detection rate of advanced breast cancer in Russia is still high, and treatment of such patients requires tailored and sometimes unconventional approach.